Lurasidone compared to other atypical antipsychotic monotherapies for bipolar depression: A systematic review and network meta-analysis. (17th November 2018) - Ostacher, Michael; Ng-Mak, Daisy; Patel, Pankaj; Ntais, Dionysios; Schlueter, Max; Loebel, Antony
Abstract: Objectives: To assess the efficacy and tolerability of lurasidone versus other atypical antipsychotic monotherapy agents in patients with bipolar depression, using a Bayesian network meta-analysis. Methods: Fourteen randomised clinical trials (6221 patients) of lurasidone, quetiapine (extended release and immediate release), aripiprazole, olanzapine, and ziprasidone for bipolar depression were included. Efficacy assessments included change in the Montgomery–Åsberg Depression Rating Scale (MADRS), rates of response (≥50% improvement in MADRS) and remission (MADRS ≤12 at study endpoint), and change in the Clinical Global Impressions–Bipolar Disorder–Severity (CGI-BP-S) scale. Tolerability outcomes included weight, somnolence, extrapyramidal symptoms (EPS), and all-cause discontinuation. Changes from baseline or odds ratios (OR) with 95% credible intervals (CrI) were evaluated. Results: Improvement in the MADRS associated with lurasidone treatment was significantly greater than placebo (–4.70, 95%CrI: –7.20, –2.21), aripiprazole (–3.62, 95%CrI: –7.04, –0.20), and ziprasidone (–3.38, 95%CrI: –6.68, –0.11), but not olanzapine (–0.15, 95%CrI: –3.12, 2.74) or quetiapine (0.10, 95%CrI: –2.68, 2.84). Results for improvement in the CGI-BP-S, and for response and remission were similar. Lurasidone was associated with less weight gain than olanzapine (–2.54 kg, 95%CrI: –3.42, –1.67) and quetiapine (–0.83kg, 95%CrI: –1.59, –0.08); and with lower rates of somnolence than quetiapine (OR: 0.33, 95%CrI: 0.11, 0.82) and ziprasidone (OR: 0.34, 95%CrI: 0.09, 0.93). No significant differences among atypical antipsychotic agents were observed in rates of discontinuation or in rates of EPS. Conclusions: In this network meta-analysis, lurasidone was found to be more efficacious than aripiprazole and ziprasidone, and was associated with less weight gain than quetiapine and olanzapine and less somnolence than quetiapine and ziprasidone.